China's Imports : An Empirical Analysis Using Johansen's Cointegration Approach - Yuan, Mingwei (IMF Working Papers; Working Paper ;, 1994)
In this paper, the behavior of China's imports during the period 1980-92 is studied. The estimation of cointegration and error correction mechanisms enables the separation of the long-run and short-run determinants of imports in China. The estimated cointegrating vector using Johansen's cointegration approach shows that, in the long run, China's imports are sensitive to changes in output, relative prices, and foreign exchange reserves. It also shows that the short-run output elasticity of imports is much greater than that in the long run, suggesting that import substitution may have been an important factor over the sample period. The forecasting ability of a conventional partial adjustment import function is then compared with that of the Johansen cointegration model; the Johansen model is shown to outperform the conventional one in forecasting accuracy.